2001
DOI: 10.1038/sj.bjp.0703989
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐related neuroprotective effects of chronic nicotine in 6‐hydroxydopamine treated rats, and loss of neuroprotection in α4 nicotinic receptor subunit knockout mice

Abstract: 1 The present study examined the eect of a range of doses of chronic nicotine (0.75, 1.5, 3.0 and 30.0 mg kg 71 day 71, s.c., 14 days) upon striatal dopaminergic nerve terminal survival following 6-hydroxydopamine (6-OHDA; 10 mg intrastriatal unilaterally) in rats; and the eects of acute nicotine (1 ) nicotine doses signi®cantly inhibited 6-OHDA-induced degeneration. 4 In wild-type mice, acute nicotine treatment produced signi®cant inhibition of methamphetamineinduced neurodegeneration. In a4 nAChR subunit kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 47 publications
4
151
0
Order By: Relevance
“…Other autoradiography studies of rats have demonstrated that chronic administration of nicotine increases glucose transporter (Glut1 and Glut3) densities in an array of brain areas (Duelli et al, 1998) and that chronically administered low dose nicotine is protective against neurodegenerative agents in the striatum (a model for Parkinson's Disease) (Ryan et al, 2001). …”
Section: Glutamatergic (And Other) Effects Of Nicotine/cigarette Smokingmentioning
confidence: 99%
“…Other autoradiography studies of rats have demonstrated that chronic administration of nicotine increases glucose transporter (Glut1 and Glut3) densities in an array of brain areas (Duelli et al, 1998) and that chronically administered low dose nicotine is protective against neurodegenerative agents in the striatum (a model for Parkinson's Disease) (Ryan et al, 2001). …”
Section: Glutamatergic (And Other) Effects Of Nicotine/cigarette Smokingmentioning
confidence: 99%
“…Although the nature of this variability is uncertain, it may be due to the relatively large lesion generated with MPTP. This possibility stems from findings that neuroprotection is observed in mice treated with methamphetamine and paraquat, both of which result in milder damage to the nigrostriatal dopaminergic system [24,40].…”
Section: Nicotine-mediated Protection Against Toxic Insults In Experimentioning
confidence: 99%
“…In rats, nicotine pre-treatment protects against nigrostriatal degeneration induced by the dopaminergic neurotoxin 6-hydroxydopamine or by mechanical lesions [23][24][25][26][27][28]. A neuroprotective effect of nicotine is also observed in striatum of mice in which nigrostriatal damage is induced by the selective dopaminergic neurotoxin MPTP [24,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Nicotine-mediated Protection Against Toxic Insults In Experimentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are numerous studies that suggest that nicotine may play a role in neuroprotection (Ryan et al, 2001;Guan et al, 2003;Stevens et al, 2003), prenatal nicotine exposure has been shown to have deleterious effects on the neonate's ability to respond to hypoxic challenges. Fewell et al (2001) found that offspring exposed to a prenatal nicotine dose of 6 mg/kg/day, resulting in a plasma nicotine concentration of 3578 ng/ ml, had a decreased ability to auto resuscitate after repeated exposure to hypoxia.…”
Section: Discussionmentioning
confidence: 99%